Segregation of Digital Game Users: An Empirical Comparison of Smartphones and Gaming Consoles - Sotaro Katsumata; Takeyasu Ichikohji (International Telecommunications Society (ITS), 2017)
The aim of this study is to examine the characteristics of digital game users and discuss desirable development and marketing strategies for firms. This study developed measurement scales and empirically found that there are two segments in the market: “share” and “achievement” orientation. Some users require “achievement” for games. These users play games to feel a sense of achievement and prefer well-designed games. They desire to embed the gaming experience in their minds and respect the intention of game developers and designers. Other users need to “share” with other gamers. They wish to play games with their friends and seek communication through games. These users do not need sophisticated graphics or stories while they engage in games simultaneously with their friends. These two preferences are not mutually exclusive—some consumers have both intentions.
Keywords: 330; Smartphone; Digital game; Consumer behavior